Survey of physiological races of Puccinia gruminis tritici in Brazil - Coelho, Elisa Thomaz; Silva, Ady Raul da; Barcellos, Amarilis Labes (Pesquisa Agropecuaria Brasileira, 2014)
Races 11, 11T, 11/65, 15, 15/65, 17, 17T, 17/65 and 17/63 were determined on 2092 stem rust samples collected from 1955 to 1968 in the Brazilian wheat regions. Race 17/61 was first determined on samples collected in 1960 and races 11/65 and 15/65, in 1964. The frequency of these races oscillated greatly during this period. Race 17 that was predominant until 1963, with more than 70% of the isolates, diminished in frequency down to less than 5% in 1968. Race 17/63 increased rapidly since 1963, when is was isolated for the first time, reaching more than 70% in 1968.